1989
DOI: 10.1111/j.1600-0404.1989.tb03820.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin and Parkinson's disease

Abstract: Two patients with Parkinson's disease were treated with 1 g tetrahydrobiopterin (BH4) for 5 days. Clinical improvement was not observed. In the cerebrospinal fluid (CSF) a 4-8 fold increase in the concentration of homovanillic acid (HVA), and a 3-fold increase in the concentration of 5-hydroxyindole acetic acid (5-HIAA) was measured. However, the concentration of HVA reached, was only approximately half as high, as that of patients treated with madopar (DOPA + benserazid). In urine, the excretion of HVA increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This may be due to differences in methods and procedures. In other studies, biopterin and biogenic amine metabolites were not simultaneously evaluated (2-6, 8, 13), the control pa-tients had neurological diseases (2,6,8), the patients' conditions were not described in detail (2-5, 8, 13) or there was a relatively small number of patients (2)(3)(4)(5)(6)13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to differences in methods and procedures. In other studies, biopterin and biogenic amine metabolites were not simultaneously evaluated (2-6, 8, 13), the control pa-tients had neurological diseases (2,6,8), the patients' conditions were not described in detail (2-5, 8, 13) or there was a relatively small number of patients (2)(3)(4)(5)(6)13).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been discovered that the level of biopterin in cerebrospinal fluid (CSF) is altered in many neurological disorders, i.e. decreased in phenylketonuria due to biopterin deficiency (1), Parkinson's disease (2,3), Alzheimer's disease (4), depression (1), hereditary progressive dystonia with marked diurnal fluctuation (5) and autistic behaviour (6); and increased in inflammation of the central nervous system in the acute phase (1,7) and in Rett syndrome (8).…”
mentioning
confidence: 99%
“…Amantadine did not change HVA levels (Cox et al, 1973). Tetrahydrobiopterin (Dissing et al, 1989) and L-threo-3,4-dihydroxyphenylserine (precursor or noraderenalin or norepinephrine –NE) (Maruyama et al, 1994) increased CSF HVA levels in PD patients, but to a lesser extent than levodopa.…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
“…Gumpert et al (1973) described an association between relatively low pre-treatment CSF 5-HIAA levels with a good response to levodopa, while Davidson et al (1977) reported this association with higher CSF 5-HIAA levels, and others found no such relation (Granerus et al, 1974). Tetrahydrobiopterin increased (Dissing et al, 1989), and L-threo-3,4-dihydroxyphenylserine decreased (Maruyama et al, 1994) CSF 5-HIAA levels.…”
Section: Neurotransmitters Neuromodulators and Related Substancesmentioning
confidence: 99%
“…Early research showed that peripherally administered BH 4 do enter the brain [5] and increase the concentration of some neurotransmitters in the brain [6]. It has also been reported that the administration of BH 4 can improve the clinical symptoms of some diseases which are caused by abnormal monoamine metabolism, such as Parkinson's disease [7] and depression [8]. The relationship between BH 4 and monoamine neurotransmitters [9] can be described as in Fig.…”
Section: Introductionmentioning
confidence: 99%